Moving the Needle Toward Fair Compensation in Pediatric Nephrology - Weidemann, Darcy K.; Ashoor, I. A.; Soranno, D. E.; Sheth, R.; Carter, C.; Brophy, P. D. (Frontiers in Pediatrics, 2022)
Remuneration issues are a substantial threat to the long-term stability of the pediatric nephrology workforce. It is uncertain whether the pediatric nephrology workforce will meet the growing needs of children with kidney disease without a substantial overhaul of the current reimbursement policies. In contrast to adult nephrology, the majority of pediatric nephrologists practice in an academic setting affiliated with a university and/or children's hospital. The pediatric nephrology service line is crucial to maintaining the financial health and wellness of a comprehensive children's hospital. However, in the current fee-for-service system, the clinical care for children with kidney disease is neither sufficiently valued, nor appropriately compensated. Current compensation models derived from the relative value unit (RVU) system contribute to the structural biases inherent in the current inequitable payment system. The perceived negative financial compensation is a significant driver of waning trainee interest in the field which is one of the least attractive specialties for students, with a significant proportion of training spots going unfilled each year and relatively stagnant growth rate as compared to the other pediatric subspecialties. This article reviews the current state of financial compensation issues plaguing the pediatric nephrology subspecialty. We further outline strategies for pediatric nephrologists, hospital administrators, and policy-makers to improve the landscape of financial reimbursement to pediatric subspecialists. A physician compensation model is proposed which aligns clinical activity with alternate metrics for current non-RVU producing activities that harmonizes hospital and personal mission statements.